809 Phase 2 trial of neoadjuvant and adjuvant PD-1 checkpoint blockade in local-regionally advanced, resectable HNSCC indicates pathological response is associated with high disease-free survival. (9th November 2020) - Wise-Draper, Trisha; Gulati, Shuchi; Takiar, Vinita; Palackdharry, Sarah; Worden, Francis; Old, Matthew; Kaczmar, John; Dunlap, Neal; Hinrichs, Benjamin; Bell, Diana; Patil, Yash; Riaz, Muhammad Kashif; et al.
Abstract : Background: Patients with newly diagnosed, resected, head and neck squamous cell carcinoma (HNSCC) with high-risk (positive margins, extracapsular spread [ECE]) or intermediate-risk pathological features have an estimated 1-year disease free survival (DFS) of 65% and 69%, respectively. 1 PD-1/PD-L1 immune checkpoint blockade has improved survival of patients with recurrent/metastatic HNSCC, and preclinical models indicate radiation upregulates PD-L1. 2 Therefore, we hypothesized that pre and post-operative administration of the PD-1 inhibitor pembrolizumab would improve 1-year DFS for patients with resectable, loco-regionally advanced (clinical T3/4 and/or ≥2 nodal metastases) HNSCC (NCT02641093 ). Methods: Eligible patients received pembrolizumab (200 mg I.V. x 1) 1-3 weeks before resection. Adjuvant pembrolizumab (q3 wks x 6 doses) was administered with weekly cisplatin (40mg/m2 X 6) and radiation (60-66Gy) for those with high-risk features and radiation alone for patients with intermediate-risk features. The primary endpoint was DFS, which was compared by log-rank test to historical controls (RTOG 9501). Evidence of pathological response to neoadjuvant pembrolizumab was evaluated by comparing pre- and post-surgical tumor specimens for treatment effect (TE) defined as tumor necrosis and/or histiocytic inflammation and giant cell reaction to keratinaceous debris. Response was classified as none (NPR, <20%), partial (PPR, ≥20% and <90%) and major (MPR, ≥90%) pathological response. Gene expression analysis in paired tumor specimens was evaluated by Nanostring. Results: Sixty-six of 84 enrolled patients had received adjuvant pembrolizumab and therefore were evaluable for DFS at the time of interim analysis. Patient characteristics included: median age 59 (range of 27 – 76) years; 30% female; 85% oral cavity, 11% larynx, and 2% human papillomavirus negative oropharynx; 85% clinical T3/4 and 68% ≥2N; 41(51%) high-risk (positive margins, 49%; ECE, 80%). At a median follow-up of 16 months, 1-year DFS was 66% (95%CI 0.48-0.84) in the high-risk group (p=1) and 91% (95%CI 0.79-1) in the intermediate-risk group (versus 69% in RTOG 9501, p=0.05) (figure 1). Among 70 patients evaluable for pathological response, TE was scored as NPR in 40, PPR in 27, and MPR in 3 patients. Patients with pathological response that were also evaluable for DFS (PPR + MPR) had significantly improved 1-year DFS when compared with those with NPR (100% versus 57%, p=0.0033; HR = 0.18 [95%CI 0.05-0.64]) (figure 2). PPR/MPR was associated with robust macrophage infiltration via Nanostring. Conclusions: Neoadjuvant and adjuvant pembrolizumab led to high DFS in intermediate-risk, but not high-risk, resected HNSCC patients. Pathological response to neoadjuvant pembrolizumab was associated with high 1-year DFS. Acknowledgements: We'd like to acknowledge the UCCC clinical trials office for their hard work on this study as well as our patients. We'd also like to acknowledge Merck & Co, Inc as they partially funded the clinical trial. Trial Registration: NCT02641093 Ethics Approval: This study was approved by the University of Cincinnati IRB with approval number 2015-6798 References: Cooper JS, Pajak TF, Forastiere AA, et al. Postoperative concurrent radiotherapy and chemotherapy for high-risk squamous-cell carcinoma of the head and neck. N Engl J Med 2004;350(19):1937-1944. doi:10.1056/NEJMoa032646 Oweida A, Lennon S, Calame D, et al. Ionizing radiation sensitizes tumors to PD-L1 immune checkpoint blockade in orthotopic murine head and neck squamous cell carcinoma. Oncoimmunology 2017;6(10):e1356153. Published 2017 Aug 3. doi:10.1080/2162402X.2017.1356153